2020
DOI: 10.1101/2020.12.14.422743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maladaptive oxidative stress cascade drives type I interferon hyperactivity in TNF activated macrophages promoting necrosis in murine tuberculosis granulomas

Abstract: Tuberculosis remains a critical infectious disease world-wide. The development of novel therapeutic strategies requires greater understanding of host factors that contribute to disease susceptibility. A major unknown in TB pathogenesis is the mechanism of necrosis in TB granulomas that leads to the massive lung tissue damage and cavity formation necessary for the pathogen transmission. In humans, TB progression has been linked to hyperactivity of type I IFN (IFN-I) pathway, the primary cause of which remains e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 80 publications
5
9
0
Order By: Relevance
“…In addition to enhanced type I IFN responses to TNFa, we also observed that both B6.Sst1 S and Sp140 -/-BMMs show increased cell death in vitro upon stimulation with polyI:C compared to B6 BMMs, as measured by lactate dehydrogenase (LDH) release (Figure 3 figure supplement 1). This result is analogous to previous findings that B6.Sst1 S BMMs die upon sustained TNF stimulation (Brownhill et al, 2020). The enhanced polyI:C-induced LDH release in both Sp140 -/and B6.Sst1 S BMMs was blunted upon genetic deletion of Ifnar (Figure 3 figure supplement 1), consistent with type I IFNs playing an important role in the cell death phenotype.…”
Section: Sp110supporting
confidence: 90%
See 1 more Smart Citation
“…In addition to enhanced type I IFN responses to TNFa, we also observed that both B6.Sst1 S and Sp140 -/-BMMs show increased cell death in vitro upon stimulation with polyI:C compared to B6 BMMs, as measured by lactate dehydrogenase (LDH) release (Figure 3 figure supplement 1). This result is analogous to previous findings that B6.Sst1 S BMMs die upon sustained TNF stimulation (Brownhill et al, 2020). The enhanced polyI:C-induced LDH release in both Sp140 -/and B6.Sst1 S BMMs was blunted upon genetic deletion of Ifnar (Figure 3 figure supplement 1), consistent with type I IFNs playing an important role in the cell death phenotype.…”
Section: Sp110supporting
confidence: 90%
“…However, much more indirect mechanisms are also possible. Recent studies suggest that hyper type I IFN responses in TNF-stimulated B6.Sst1 S BMMs derive from aberrant oxidative stress that activates the kinase JNK and ultimately results in a non-resolving stress response that promotes necrosis (Bhattacharya et al, 2021;Brownhill et al, 2020). Interestingly, mouse SP140 localizes to nuclear structures called PML bodies.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously reported that TNF induces higher levels of type I IFN-induced genes in Sst1 S BMMs as compared to B6 BMMs (Bhattacharya et al, 2021;Ji et al, 2019). We also observed higher levels of Ifnb transcripts in the lungs of B6.Sst1 S mice infected with M. tuberculosis, as compared to infected B6 mice (Ji et al, 2019 (Brownhill et al, 2020). The enhanced polyI:C-induced LDH release in both Sp140 -/and B6.Sst1 S BMMs was blunted upon genetic deletion of Ifnar (Figure 3  figure supplement 1), consistent with type I IFNs playing an important role in the cell death phenotype.…”
Section: Enhanced Type I Ifn Responses In Sp140supporting
confidence: 78%
“…We expect that future mechanistic studies will be critical to further confirm this conclusion. stress that activates the kinase JNK and ultimately results in a non-resolving stress response that promotes necrosis (Bhattacharya et al, 2021;Brownhill et al, 2020). Interestingly, mouse SP140 localizes to nuclear structures called PML bodies.…”
Section: Sp140mentioning
confidence: 99%
“…This unique necrotic granuloma phenotype is controlled by a single genetic locus sst1 (supersusceptibility to tuberculosis-1), which has been characterized in our previous studies (27)(28)(29)(30)(31). We have shown that this locus controls macrophage responses to TNF and the sst1 susceptibility allele reduces macrophage stress resilience and increases type I interferon production (32)(33)(34)(35). It has been shown to control host resistance to several taxonomically unrelated intracellular bacterial pathogens (32,36,37).…”
Section: Introductionmentioning
confidence: 89%